Application Research of Parallel Redundancy Structure of the Power on Electric Locomotive Based on CAN - 张玉平; 王玉松 (机车电传动)
This paper researched the 110V power supply for electric locomotive, which used TI’s TMS320F2812 digital signal processing chip as the CPU and adopts the double closed-loop controlling (voltage loop outside, current loop inside). The message were transferred through the CAN bus and intelligent current-sharing of the parallel modules had been realized by using the software. The experiments show that the power with load run stably and current-sharing effects is well.